History of Inheritance of Wayang Topeng Malangan (Malang Traditional Mask Puppet) in Pakisaji and Tumpang (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2020)
This study aims to explain the history and process of inheriting mask puppet art in two representative hermitages (padepokan) (in Malang, namely Padepokan Asmoro Bangun in Pakisaji sub-district and Mangun Dharma in Tumpang sub-district). This research uses a qualitative approach. Data collection techniques are done through interviews, observation, and study documents. The process of inheritance includes art practices such as dancing, puppeteering, playing musical instruments, and making masks and transferring knowledge about Wayang Topeng Malangan. Inheritance is generally done since offsprings (children/grandchildren) are still at an early age. The history of the inheritance of the traditional mask puppet art in Padepokan Asmoro Bangun has occurred for six generations of this family since before 1930 starting from the Serun period. The sixth Padepokan Asmoro Bangun Heirs are two daughters named Winnie Padnecwara (15 years old) and Dita Andhika Raja Padmi (12 years old) who learned this art since the age of four. Padepokan Mangun Dharma is the home of mask puppet art, as well as music, traditional dance, and theatre, macapat, puppetry, and shadow puppets. The history of the inheritance of this hermitage began with the great-grandfather of the puppeteer Soleh namely Kek Sainten (Grandpa Sainten). The current heir of Padepokan Mangun Dharma is the son of the puppeteer Soleh, Supriyono Hadi Prasetyo, who also learned puppetry both autodidact and formally through college. Although inheritance occurs vertically, which is hereditary in each hermitage, horizontal inheritance also occurs between the two. This indicates that the inheritance process of Padepokan Asmoro Bangun and Mangun Dharma are related to each other.Â